Synergistic effects of gelatin and convection on copper foil electrodeposition. (1st September 2016) - Chang, Tingru; Jin, Ying; Wen, Lei; Zhang, Chensheng; Leygraf, Christofer; Wallinder, Inger Odnevall; Zhang, Junping
Graphical abstract: Highlights: As an additive on copper foil electrodeposition, gelatin restrains the copper grain growth in the lateral direction parallel to the surface. Gelatin causes the increase of the local misorientation and of the internal stresses on both the shiny and the matte sides. Hydrogen gas release is accelerated at strong convection but hindered by gelatin. Spiral-shaped pattern forms on the matte side of copper foil at strong convection in the presence of gelatin. Abstract: Copper foil electrodeposition has been explored using a pure titanium rotating disk electrode (RDE) in acidic electrolytes containing gelatin and/or chloride ions under different convection conditions. In the plating bath without gelatin, the results indicate that stronger convection promotes hydrogen evolution, which reduces the current efficiency during copper plating. Gelatin restrains the growth of copper grains in the lateral direction parallel to the surface. This results in grain refinement on the shiny side, an increase in local grain misorientation and in internal stresses on both the shiny and the matte side, and a reduction in their internal stress difference. At strong convection conditions and with gelatin present, copper deposits as strip-like grains along the centrifugal direction of the cross section, and finally forms a spiral-shaped pattern on the matte side. The causes of these features are discussed in detail. The combined influences of hydrogen and gelatin adsorption are further elaborated in a model for a copper deposition. The current investigation suggests that a moderate convection (somewhat lower than 1000 rpm) and a concentration of 2 ppm gelatin in the plating bath are sufficient for copper foil fabrication in the presence of chloride ions (20 ppm).